Methylphenidate Use and Infectious Diseases in Children With Attention Deficit and Hyperactivity Disorder: A Population-Based Study - Chen, Vincent Chin-Hung; Kao, Kai-Liang; Chen, Yi-Lung; Wu, Shu-I; Lee, Min-Jing; Gossop, Michael (Frontiers in Medicine, 2022)
Objective: Children with attention deficit hyperactivity disorder (ADHD) have more visits to the emergency department (ED) due to injuries than those without ADHD. However, no study has investigated whether children with ADHD have more ED visits or hospitalizations due to infectious diseases (ID) and whether methylphenidate treatment may reduce the risk. Method: The incidence of ID- related ED visits or hospitalizations were defined as the main outcome. Cox regression and conditional Poisson regression models were calculated to estimate hazard ratios in the population level and relative risks for the self-controlled case series design, respectively. Results: Children with ADHD had higher rates of emergency visits (HR=1.25, 95%CI: 1.23~1.27) and hospitalizations (HR=1.28, 95%CI: 1.26~1.31) due to infectious diseases than those without ADHD. In the ADHD subgroup, those who received methylphenidate treatment have a reduced risk of emergency visits (HR=0.10, 95%CI: 0.09~0.10) and hospitalizations (HR= 0.73, 95% CI: 0.71~0.75), compared to those without treatment. The risk of infectious disease- related emergency visits decreased to 0.21 (95%CI: 0.21~0.22); and hospitalizations decreased to 0.71 (95%CI: 0.69~0.73). Within self-controlled analysis also demonstrated that compared to non- methylphenidate exposed period, children with ADHD had significantly decreased risks for infection- related emergency visits (RR=0.73, 95%CI: 0.68~0.78) or hospitalizations (RR=0.19, 95%CI: 0.17~0.21) during methylphenidate-exposed periods. Conclusions and Relevance: This is the first study that reported an increased risk of infectious diseases- related healthcare utilizations in children with ADHD compared to those without, and that such risks may be significantly reduced in ADHD children that received methylphenidate treatment.